Haemaphysalis longicornis Neumann 1901 - Heath, Allen C. G.; Palma, Ricardo L.; Cane, Rachel P.; Hardwick, Scott (Zenodo, 2011)
Haemaphysalis longicornis Neumann, 1901 Host(s) Land birds: Apteryx mantelli , Gallus gallus gallus, Phasianus colchicus , Meleagris gallopavo , Anas platyrhynchos platyrhynchos , Circus approximans , Gallirallus philippensis assimilis , Gallirallus australis greyi , Alauda arvensis , Turdus philomelos , Acridotheres tristis , Passer domesticus , Emberiza citrinella . Mammals: Capra hircus , Bos taurus , Ovis aries , Canis familiaris , Dama dama, Cervus elaphus , Cervus timorensis , Cervus unicolor , Equus asinus , Equus caballus , Erinaceus europaeus , Felis catus , Lepus europaeus , Oryctolagus cuniculus , Rattus rattus , Rattus norvegicus , Mus musculus , Mustela furo , Mustela nivalis , Mustela erminea , Sus scrofa, Trichosurus vulpecula , Homo sapiens . Distribution World: Japan, China, former USSR, Korea, Australia (south-eastern Queensland, coastal New South Wales and Victoria; localised population in Western Australia), New Caledonia, Fiji, Western Samoa, Tonga, Vanuatu; (not established in Hawaii, contra Cane 2011, last updated 2010). New Zealand: Widespread in northern half of North Island, as far south as Waikanae in the west and Hastings in the east. There have been what appear to be only temporary infestations at Longbush (south Wairarapa) in 2000–2002 (W. Shaw, pers. comm. February 2011) and at nearby Pirinoa (A.C.G. Heath unpublished). In the South Island, it is established in Golden Bay and north of Hokitika, and there has been a temporary infestation in Southland. References: Neumann (1901); Dumbleton (1953, 1973); Hoogstraal et al . (1968); Roberts (1970); Besier & Wroth (1985); Heath (1977, 1981, 1985, 2000, 2010a, b); Bishop & Heath (1998); Tenquist & Charleston (2001); Gordon (2010); Cane (2011, last updated 2010). Published as part of Heath, Allen C. G., Palma, Ricardo L., Cane, Rachel P. & Hardwick, Scott, 2011, Checklist of New Zealand ticks (Acari: Ixodidae, Argasidae), pp. 55-63 in Zootaxa 2995 on page 58, DOI: 10.5281/zenodo.203775